Motion Detection Algorithm for Unmanned Aerial Vehicle Nighttime Surveillance - ZHANG, Maojun; LIU, Yu; WANG, Wei; XIAO, Huaxin (IEICE Transactions on Information and Systems, 2014)
In consideration of the image noise captured by photoelectric cameras at nighttime, a robust motion detection algorithm based on sparse representation is proposed in this study. A universal dictionary for arbitrary scenes is presented. Realistic and synthetic experiments demonstrate the robustness of the proposed approach.